Factors Influencing Consumers’ Resistance Towards Property Rental Payments In Proptech Apps - Jasmine Shafira; Prawira Fajarindra Belgiawan (Eduvest - Journal of Universal Studies, 2024)
This study investigates the reasons behind resistance to using the payment functionalities of proptech apps among users who have adopted the search features but not the payment feature. To explore this, the study employs Innovation Resistance Theory (IRT), mixed with variables from UTAUT2. Previous research showed that various barriers can influence user resistance to app payments. A mixed-methods approach is used in this research, combining qualitative preliminary testing and quantitative main testing. The study adopts convenience sampling to gather data. Data were collected through questionnaire and analyzed using Multiple Linear Regression Analysis in SPSS 27.0. The findings reveal that three main barriers—Risk, Tradition, and Image—significantly influence users from making payments through proptech apps. The Risk Barrier pertains to concerns over security and privacy. The Tradition Barrier involves users' preference for conventional method ways over alternatives. The Image Barrier relates to the perception of the app's reputation and trustworthiness. Future research recommendation include conducting discriminant analysis to compare non-adopters of proptech app payments distinct groups, incorporate demographic elements such as age, income, and gender as moderating variables and including additional independent variables that can expand the research scope. This study contributes to the existing literature by addressing user resistance to increase the adoption of digital payment functionalities in proptech applications. The findings can help app developers and marketers design better strategies to overcome these barriers and promote wider acceptance of proptech app payments.